Quality management and a balanced scorecard as supporting frameworks for a new management model and organisational change - Pimentel, L.; Major, M. J. M. F. (16th QMOD Proceedings. Quality Management and Organizational Development Conference, 2013)
Purpose: The purpose of this paper is to examine how the implementation of quality management and total quality management (TQM) in particular contribute to organizational change in organizations, and also to analyse the impact of integration of TQM and a balanced scorecard (BSC) in a new management model and in the effectiveness of an organization. Methodology/Approach: The paper adopts a descriptive longitudinal case study, and deals with the implementation of innovative management frameworks in a Portuguese government agency. The implementation of the frameworks followed two separated pillars: i) a quality management programme, based on TQM (encompassing CAF, ISO 9001, and a quality manual); and ii) a performance measurement programme translated basically into a BSC. The study was carried out within the scope of an organizational change process which lasted for several years. To support the investigation and the development of the case study, a research design was defined. Collection of evidence comprised the conduction of 47 interviews (in three different phases between January 2010 and February 2012, including a pilot study), and also the analysis of data and written documentation. The study was built on quality management and performance measurement systems (PMS) (including BSC) literature. Findings: The new management model of the organisation, based on a quality management programme (TQM in particular), and on a performance measurement programme (translated basically into a BSC) proved to be efficient in practice. Secondly, TQM contributed to organisational change and to the increase of financial performance in the organisation. Finally, TQM and BSC were duly integrated and linked to the strategic plan. Research implications: The paper contributes to the literature on quality management, by highlighting the role of quality management and TQM in particular as important tools to help organizations to change and to improve efficiency and financial performance. It also contributes to show that organizations in general can integrate successfully quality management and PMS, including BSC. These implications are important for academics as well as for practitioners. Originality/Value of the paper: The present case study helps to close the gap associated with the fact that few case studies or surveys have been conducted so far in scientific literature regarding the successful integration between BSC and quality management tools. Furthermore, this integration is visualized in a government agency where few practical situations have been found. Moreover, the paper confirms the assumption that quality management is a key factor to emphasize organisational and cultural change in organisations.